Work Motivation and Work Environment as Determinants of Job Satisfaction Among Generation Z: Evidence from Greater Bandung Indonesia - Kheysifa Fedria; Kiki Sudiana (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2026)
This study aims to examine the influence of work motivation and work environment on job satisfaction among Generation Z employees in Greater Bandung. As the fastest-growing cohort in the workforce, Generation Z possesses distinct characteristics and expectations that, when unmet, can lead to job dissatisfaction, reduced work engagement, and elevated turnover intention underscoring the urgency for organizations to understand the determinants of their job satisfaction. This study used quantitative methods with a descriptive and causal approach. Data were obtained through questionnaires distributed to respondents who were Generation Z employees in the Greater Bandung area. The data analysis technique used was multiple linear regression analysis to determine the influence of work motivation and the work environment on job satisfaction. The independent variables in this study were work motivation and the work environment, while the dependent variable was job satisfaction. The results of this study are expected to provide an overview of the conditions of work motivation, the work environment, and the level of job satisfaction among Generation Z in Greater Bandung. Furthermore, this research is expected to demonstrate the influence of work motivation and work environment on job satisfaction, both partially and simultaneously. This research is expected to provide theoretical contributions to the development of human resource management science and provide practical input for organizations in managing the Generation Z workforce more effectively and in accordance with the characteristics of this generation. Keywords : Work Motivation, Work Environment, Job Satisfaction, Generation Z